Sosialisasi Pemanfaatan Chatgpt Sebagai Pendukung Alat Pembelajaran Bagi Guru SMP PGRI 8 Sidoarjo - Vigih Hery Kristanto; Eka Nurmala Sari Agustina; Tanti Diyah Rahmawati; Diyah Purwitasari (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2024)
In the ever-evolving digital era, education faces unprecedented challenges and opportunities. Technology is now an integrated part of the learning process, providing various tools that can increase the effectiveness and efficiency of education. One technological innovation that has great potential to support educators is ChatGPT. This ability can be utilized by teachers for various purposes, including in making learning tools. With the help of ChatGPT, teachers can save time and energy in designing teaching materials, assignments and learning evaluations that suit students' needs (Kharis et al., 2024). The teachers at SMP PGRI 8 Sidoarjo have not made much use of technology that makes it easier for them to prepare learning tools. This can be seen from the results of initial observations which show that 71.4% of teachers have never used applications or technology that makes it easier to create learning tools. This Community Service implementation was carried out with the aim of introducing, socializing and assisting teachers in utilizing ChatGPT to develop learning tools more quickly, effectively and efficiently. The results of participant responses regarding the implementation of activities are measured by participant satisfaction, which is the average of participant satisfaction with the satisfaction indicator factors. In this activity, 84.46% of participants gave an average rating of very good to the statement items in the questionnaire, which can be interpreted as meaning that 84.46% of participants were very satisfied.